Transport and Communications Plan Statistics May 1971 - Planning Commission (Planning Commission, 1971)
For some time past the need for compilation of Plan Statistics relating to transport and communications has been greatly felt. A good deal of information is, no doubt, available about this sector in various publications of the Ministries of Railways, Shipping and Transport, Tourism and Civil Aviation and the Planning Commission. However, key data pertaining to different modes of transport are not available at one place, particularly those which would give a picture of the developments in transport and communications during different Plan periods in financial and physical terms and could be readily referred to in dealing with problems of transport planning.
Government of India, Planning Commission (Transport Division)
Government of India, Planning Commission (Transport Division)